Physical Activity and Body Composition Are Associated With Severity and Risk of Depression, and Serum Lipids - von Zimmermann, Claudia; Winkelmann, Merle; Richter-Schmidinger, Tanja; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2020)
Background: Physical activity and a healthy body composition are said to reduce the risk of major depressive disorder. Nonetheless, deeper insight is needed into which specific forms of physical activity (and their relation to body composition) are effective in improving and preventing depressive symptoms. Methods: We compared different self-reported physical activities of the Global Physical Activity Questionnaire and body composition measures between patients with a current major depressive episode (MDE; N = 130) and healthy control subjects (N = 61). These parameters were also tested for correlations with depression severity and serum lipid levels in patients and controls. Results: Patients with a current MDE reported significantly fewer hours spent on total physical activity, walking or bicycling for travel, and vigorous-intensity activities at leisure than healthy control subjects. More time spent on vigorous-intensity activities at work, less time spent on walking or bicycling for travel, higher body fat mass, and lower body muscle mass correlated significantly with stronger depression severity. Physical activity and body measures correlated significantly with serum lipid levels. Limitations: Self-reports of physical activity, only short-term follow-up of 20 days, cross-sectional study design without examination of causal role of exercise. Conclusions: More time spent on traveling by foot or by bike is especially associated with a lower risk of and milder depression. These results highlight the differential role of physical activity in depression.
CRIS-Team Scopus Importer:2020-06-30
Keywords: body composition; depression; mental health; physical activities and sports; serum lipid concentration